Problems and Prospects of Manufacturing Industries in Nepal - Mainali, Pradip Kumar (Economic Journal of Nepal, 2015)
This study aims to examine the problems and prospects of manufacturing industries in Nepal based upon the responses obtained from investors, regulators, and independent intellectuals. Chi-square test is performed to check the validity of views from different groups of respondents and weight basis responses are ranked. It is perceived that the power outage, labour related problems, poor infrastructural development, shortcomings on industrial policies as being the major problems of Nepalese manufacturing despite there are bureaucratic impediment and poor managerial skills of manufacturer. Internal resource based production and internal market based production following comparative advantage productions are opined as prospects of Nepalese manufacturing. Problems inside the industrial estates such as poor infrastructure, less electricity facilitation and low voltage, no place for extension are also the subsequent causes of poor manufacturing development.